Analysis Study to Develop a Death Management Module with Islamic Sharia based on QR Code - Najikhah, Fatikhatun; Situmorang, Robinson; Sukarjo, Moch. (International Journal of Psychosocial Rehabilitation, 2020)
The obligation of a Muslim for a fellow Muslim who has died is to take care of his body. How to treat corpses needed by Islam by bathing, believing, praying, and then burying. Some people don’t learn and understand it; even very few can do it correctly, according to Sharia. Based on beliefs to help develop education in the community, it is necessary to study the research needs of the community to get learning products that are truly in accordance with needs. The purpose of this study is to produce an analysis of the organizing body’s learning needs. This study uses a participatory method with various data collection tools such as interviews, questionnaires, and documentation. This research was conducted on prospective students of the Institut Manajemen Kematian DKI Jakarta. Preliminary research results indicate that the Institut Manajemen Kematian requires a module to train the organization of the body.